Physiological Parameters Monitoring System for Occupational Safety - Lukocius, R.; Vaitkunas, M.; Virbalis, J. A.; Dosinas, A.; Vegys, A. (Elektronika ir Elektrotechnika, 2014)
A wireless physiological parameters monitoring system designed for workers to observe their health conditions during daily activities was proposed and analyzed in our work. This system meant to protect people from accidents and sudden health impairments at work. The key part of the system is wearable sensors that follow human respiratory function and cardiovascular system work. Remote computer evaluates one’s health condition by tracking the abnormal deviations of the two main physiological parameters – heart rate and respiratory rate. Attention in this paper was focussed on suppression of the signal noise caused by body movement artefacts. Some new algorithms of the data processing were developed to this end. The proposed monitoring system was assembled and calibrated against standard medical monitor. Results of the system accuracy test are presented in this paper. DOI: http://dx.doi.org/10.5755/j01.eee.20.5.7100